Metabolic dysfunction-associated steatotic liver disease: ferroptosis related mechanisms and potential drugs - Zhu, Baoqiang; Wei, Yuankui; Zhang, Mingming; Yang, Shiyu; Tong, Rongsheng; Li, Wenyuan; Long, Enwu (Frontiers in Pharmacology, 2023)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is considered a “multisystem” disease that simultaneously suffers from metabolic diseases and hepatic steatosis. Some may develop into liver fibrosis, cirrhosis, and even hepatocellular carcinoma. Given the close connection between metabolic diseases and fatty liver, it is urgent to identify drugs that can control metabolic diseases and fatty liver as a whole and delay disease progression. Ferroptosis, characterized by iron overload and lipid peroxidation resulting from abnormal iron metabolism, is a programmed cell death mechanism. It is an important pathogenic mechanism in metabolic diseases or fatty liver, and may become a key direction for improving MASLD. In this article, we have summarized the physiological and pathological mechanisms of iron metabolism and ferroptosis, as well as the connections established between metabolic diseases and fatty liver through ferroptosis. We have also summarized MASLD therapeutic drugs and potential active substances targeting ferroptosis, in order to provide readers with new insights. At the same time, in future clinical trials involving subjects with MASLD (especially with the intervention of the therapeutic drugs), the detection of serum iron metabolism levels and ferroptosis markers in patients should be increased to further explore the efficacy of potential drugs on ferroptosis.